Kinetic Stability and Operational Optimization of Turbidimetric Sulfate Analysis Based on SNI 6989.20:2019 Methodology - Uswatul Husna; Syamsi Aini (International Journal of Science and Environment (IJSE), 2026)
The measurement of sulfate (SO₄²⁻) levels using the SNI 6989.20:2019 turbidimetric method is highly dependent on the stability of the barium sulfate (BaSO₄) suspension. This study aims to evaluate the effect of waiting time (standing time) variations ranging from 5 to 35 minutes and sample container handling protocols (single vs. multi-Erlenmeyer) on the accuracy of analytical results at concentration levels of 20 mg/L and 60 mg/L. Measurements were conducted using a UV–Vis spectrophotometer at a wavelength of 420 nm. The results indicated that, at low concentrations (20 mg/L), the suspension remained relatively stable, with recovery values within the acceptable limits (90–110%) up to 35 minutes. Conversely, at high concentrations (60 mg/L), a significant decrease in recovery was observed after the 10-minute threshold, reaching 77.83% at 35 minutes due to particle sedimentation. The multi-Erlenmeyer protocol provided more accurate kinetic data compared to the single-Erlenmeyer approach, which tended to produce positively biased results due to mechanical re-suspension effects during repeated sampling.It is concluded that strict adherence to a 5-minute waiting time window is essential to ensure the validity of water quality monitoring, particularly for samples with high pollutant loads. Keywords: Sulfate, Turbidimetry, SNI 6989.20:2019, Waiting Time, Kinetic Stability